PEMANFAATAN AGREGAT PLASTIK PADA PEMBUATAN BATA BETON - Azha Zayda Fasani; Ferina - Rahmasari; Tri - Hastuti; Triastuti - Triastuti (Rekayasa Sipil, 2022)
The increased demand for red bricks or concrete bricks has resulted from the increase in house construction. Meanwhile, raw materials for making red bricks are becoming limited. As a result, alternative materials are required in the production of concrete bricks. On the other hand, even more plastic disposed of in landfills and cannot be recycled. As a consequence, the use of plastic waste is assumed to be a solution to the problem of plastic waste including the availability of raw materials for making concrete bricks. This research used artificial aggregate of plastic recycle (LDPE) which derived from cap bottle or plastic bag. The purpose of this research is to know the influence of plastic aggregate utilizing on the brick. The testing were compressive strength, density and permeability as SNI 03-0349-1989 about brick. The bricks in the research used plastic aggregated which the maximum diameter was 4 mm.Â  The percentages of plastic aggregate are between 5% until 25% as replacement of sand. The results show 50 kg/cmÂ² of the maximum compressive strength, 1667 gr/cm3 for density and 10% for water absorption. Based on SNI 03-0349-1989, the brick in this research was the brick with class III.